Implementation of Differentiated Learning in the Independent Curriculum for Fifth-Grade Science at SDN 31 Kampung Caniago, Agam Regency - Fadli S; Rayendra; Zelhendri Zen; Abna Hidayati (Jurnal Penelitian Pendidikan IPA, 2026)
This study examines the effect of differentiated learning within the Independent Curriculum on students’ mastery of science content and creative thinking skills in Grade V at SDN 31 Kampung Caniago, Agam Regency. The research was motivated by the need for student-centered instruction that accommodates diverse learning needs and supports 21st-century competencies. A quantitative descriptive method with a one-shot case study design was employed. The sample consisted of 27 students selected through purposive sampling. Data were collected using observation and documentation, supported by a performance assessment instrument based on five indicators of creative thinking: fluency, flexibility, originality, elaboration, and evaluation. Data were analyzed using percentage scores and N-gain. The results showed that students’ mastery of science content reached a high level, with the highest achievement in the topic Properties and Changes of Matter (88%) and the lowest in the Solar System (75%). Creative thinking skills also improved, as indicated by an increase in N-gain from 0.63 during the preparation phase to 0.72 during the presentation phase. These findings demonstrate that differentiated learning effectively enhances both content mastery and creative thinking in elementary science learning.